Evaluating the Health Belief Model Constructs in Adopting the HPV Preventive Behavior - Solmaz Mohamadi; Zeinab Rabiei; Zahra sadat Pajohideh; Zahra Barati; Seyedeh Solmaz Talebi; Afsaneh Keramat (Tehran University of Medical Sciences, 2023)
Objective: Genital warts are a highly contagious sexually transmitted disease. It is caused by the human papillomavirus (HPV), which is transmitted through sexual contact. HPV is the most important cause of cervical cancer. This study aimed to evaluate the health belief model (HBM) constructs in adopting HPV preventive behavior in women referred to comprehensive health centers in Southwestern Iran. Materials and methods: This descriptive-analytical study was performed on 1000 women referring to health centers in Ahvaz during 2019-2020 who were selected via a two-stage stratified random sampling technique. Data were collected using a valid and reliable researcher-made questionnaire based on the HBM. The data were analyzed using descriptive statistics, t-test, ANOVA, Pearson correlation coefficient, and regression analysis in SPSS v.18, at a significance level lower than 0.05. Results: Total scale reliability of the tool was very good (α=0.828), as the Intra-cluster correlation coefficient (ICC) was to be 0.86. The mean of preventive behavior using an ANOVA test was significantly different at different levels of education (P <0.05). The mean and standard deviation of knowledge about HPV and preventive behavior was moderate (11.45±3.4). Pearson correlation coefficient showed a significant direct relationship between preventive behavior with awareness, perceived sensitivity, and self-efficacy and inversely related to perceived barriers. Perceived sensitivity (0.01) and self-efficacy (<0.001) were identified as the final predictors of behavior in regression analysis. Conclusion: As the results showed, designing programs to prevent HPV, considering the perceived role of perceived sensitivity and self-efficacy, increases the likelihood of effective interventions.